Effects of Alcoholic Extract of Achillea Millefolium Flowers on Fertility Parameters in Male Rats - R Parandin (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2011)
Introduction: Fertility regulation with plant preparations has been reported in ancient literature of indigenous systems of medicine. In this research the effects of alcoholic extract of Achillea millefolium flowers on fertility indices, body weight and weight of reproductive organs was evaluated in male rats. Methods: 18 rats were randomly divided into 3 groups; control, group A and group B, each group comprising of six rats. Animals in control group received 1 ml of distilled water(vehicle) and test groups(A and B) received graded doses of 200 and 400 mg/kg body weight of alcoholic extract of Achillea millefolium flowers on a daily basis for 50 days. At the end of 50 days of treatment period, fertility indices such as body and reproductive organs weight, sperm motility and count, fertility rate, epididymal sperm reserve(ESR), daily sperm production(DSP), blood testosterone concentration and fertility rate were measured. Results: There was a significant decrease in GSI(Testes weight/body weight ratio), epididymides weight, sperm count, ESR, DSP, blood testosterone concentration and fertility rate in both the lower dose group (0, p<0.05, 0, 0, p<0.05, p<0.05, and 0) and the higher dose group(p<0.05, p<0.01, p<0.01, p<0.5, p<0.001, p<0.001 and p<0.05as compared to the control group. Conclusion: The results of this study showed that alcoholic extract of Achillea millefolium flowers in higher doses could decrease fertility in male rats.